Association between pre-diabetes and microvascular and macrovascular disease in newly diagnosed type 2 diabetes. Issue 1 (23rd April 2020) - Palladino, Raffaele; Tabak, Adam G; Khunti, Kamlesh; Valabhji, Jonathan; Majeed, Azeem; Millett, Christopher; Vamos, Eszter P
Abstract : Objective: The associated risk of vascular disease following diagnosis of type 2 diabetes in people previously identified as having pre-diabetes in real-world settings is unknown. We examined the presence of microvascular and macrovascular disease in individuals with newly diagnosed type 2 diabetes by glycemic status within 3 years before diagnosis. Research design and methods: We identified 159 736 individuals with newly diagnosed type 2 diabetes from the UK Clinical Practice Research Datalink database in England between 2004 and 2017. We used logistic regression models to compare presence of microvascular (retinopathy and nephropathy) and macrovascular (acute coronary syndrome, cerebrovascular and peripheral arterial disease) disease at the time of type 2 diabetes diagnosis by prior glycemic status. Results: Half of the study population (49.9%) had at least one vascular disease, over one-third (37.4%) had microvascular disease, and almost a quarter (23.5%) had a diagnosed macrovascular disease at the time of type 2 diabetes diagnosis. Compared with individuals with glycemic values within the normal range, those detected with pre-diabetes before the diagnosis had 76% and 14% increased odds of retinopathy and nephropathy (retinopathy: adjusted OR (AOR) 1.76, 95% CI 1.69 to 1.85; nephropathy: AOR 1.14, 95% CI 1.10 to 1.19), and 7% higher odds of the diagnosis of acute coronary syndrome (OR 1.07, 95% CI 1.03 to 1.12) in fully adjusted models at time of diabetes diagnosis. Conclusions: Microvascular and macrovascular diseases are detected in 37%–24% of people with newly diagnosed type 2 diabetes. Pre-diabetes before diagnosis of type 2 diabetes is associated with increased odds of microvascular disease and acute coronary syndrome. Detection of pre-diabetes might represent an opportunity for reducing the burden of microvascular and macrovascular disease through heightened attention to screening for vascular complications.